2002
DOI: 10.1093/jaoac/85.3.768
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Genetically Modified Crops and Their Derivatives: Critical Steps in Sample Preparation and Extraction

Abstract: The detection of genetically modified crops in foodstuff relies on detection of transgenic DNA or protein material in the sample matrix. Purified DNA or proteins are used as analytical material for polymerase chain reaction technologies and immunodiagnostics. Successful sample preparation is critical to the validity of subsequent analysis. For routine analysis, a good sample preparation technique should be simple, safe, and inexpensive while reproducibly generating DNA/protein of sufficient quality and yield. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Although it has been reported that concentrations of NaCl >25 mM inhibit PCR [19], our PCR analyses were successful despite the very high concentrations of NaCl used. Since washing the DNA pellet with ethanol removes NaCl [20], multiple washes with ethanol greatly reduce the concentration of NaCl. High concentration of EDTA prevented DNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that concentrations of NaCl >25 mM inhibit PCR [19], our PCR analyses were successful despite the very high concentrations of NaCl used. Since washing the DNA pellet with ethanol removes NaCl [20], multiple washes with ethanol greatly reduce the concentration of NaCl. High concentration of EDTA prevented DNA degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Cream is mainly composed of lipids such as oils or waxes [34,35]. Hexane or chloroform treatment minimizes PCR inhibition during DNA extraction from lipid-rich cosmetics [36,37]. However, the use of organic solvents in the extraction process is tedious and cumbersome; thus, most commercial kits do not use organic solvents.…”
Section: Detection Limit Of the Real-time Pcr Assaymentioning
confidence: 99%
“…To overcome this problem, the cetyl trimethylammonium bromide (CTAB) method can be applied with the addition of particular chemical and enzymatic treatments (Terry et al, 2002). To remove polysaccharides and proteins, treatments with enzymes such as pectinase, cellulase, hemicellulose, a-amylase, proteinase K and glycoside hydrolases can be used (Rether et al, 1993;Demeke & Jenkins, 2010).…”
Section: Molecular Fungal Detection Assaysmentioning
confidence: 99%